Clinical spectrum and outcome of paraquat poisoning in a tertiary care teaching hospital - B. R., Halesha; K., Venugopal (International Journal of Advances in Medicine, 2018)
Background: Paraquat is most common insecticide compound used for suicidal consumption in rural part of the Karnataka next to organo-phosphorous compound. It produces various local and systemic manifestations in the early course. It is very notorious to cause multi-organ dysfunction and mortality within 24 hours in severe amount of consumption. Lack of specific antidote and high-quality evidence based medicine makes the management of paraquat poisoning challenging. Hence, we took up the study to evaluate the clinical features, course and management option for the poisoning. Methods: It is an observational study conducted at HIMS, Hassan. History was collected from patient and bystanders. Clinical features, laboratory parameters were noted regularly and frequently. Patient’s complications were identified initially and treated accordingly. All the data collected were tabulated and statistically analysed. Results: Out of 110 patients, 72 were females and 38 were males; most of them were in the age group of 30-40 years. Mild poisoning was noted in 30, moderate in 56 and 24 patients were severe. Most common symptom was nausea and signs were oral cavity ulcers followed by tachycardia and tachypnoea. The overall mortality was 72%, 18% were recovered fully and 10% patients left against medical advice. Conclusions: Since there is a lack of antidote management of paraquat is challenging. Early gastric lavage, aggressive fluids, IV methyl prednisolone and N-Acetyl-Cysteine is beneficial.